2020
DOI: 10.5005/jp-journals-10005-1773
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the COVID-19 Pandemic on Dental Interns in Riyadh, Saudi Arabia: A Cross-sectional Survey

Abstract: A bstract Background Dental profession is labeled as a high-risk profession, due to which dental care professionals are under tremendous pressure during the outbreak of COVID-19 pandemic. The aim of this study was to assess the psychological impact of the COVID-19 pandemic on dental interns in Riyadh, Saudi Arabia. Materials and methods A cross-sectional study was conducted among dental interns from different universities in Riyadh, Saudi Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…About two thirds (n = 98) of the studies reported the data on depression [ 8 , 23 27 , 29 33 , 35 , 36 , 38 41 , 45 52 , 56 60 , 62 65 , 67 69 , 71 76 , 78 82 , 84 , 86 , 88 , 89 , 91 , 92 , 94 , 95 , 97 , 99 , 100 , 103 , 104 , 106 – 108 , 111 , 113 , 115 117 , 120 , 123 , 124 , 127 , 129 133 , 137 , 138 , 140 , 141 , 143 146 , 149 , 151 154 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About two thirds (n = 98) of the studies reported the data on depression [ 8 , 23 27 , 29 33 , 35 , 36 , 38 41 , 45 52 , 56 60 , 62 65 , 67 69 , 71 76 , 78 82 , 84 , 86 , 88 , 89 , 91 , 92 , 94 , 95 , 97 , 99 , 100 , 103 , 104 , 106 – 108 , 111 , 113 , 115 117 , 120 , 123 , 124 , 127 , 129 133 , 137 , 138 , 140 , 141 , 143 146 , 149 , 151 154 ,…”
Section: Resultsmentioning
confidence: 99%
“…There were 40 studies which reported on data regarding stress, using five different type of scales which were Depression-Anxiety-Stress Scale-21 (DASS-21), Safety Attitudes Questionnaire (SAQ), Perceived Stress Scales (PSS), Stanford Acute Stress Reaction Questionnaire (SASRQ), and State and Trait Anxiety Inventory (STAI) [ 30 , 31 , 39 , 56 , 59 , 77 , 78 , 91 , 92 , 99 – 102 , 104 , 106 , 107 , 113 , 120 , 123 , 124 , 127 , 129 133 , 138 , 140 , 141 , 143 , 144 , 150 , 152 , 153 , 155 , 160 , 161 , 164 , 165 ].…”
Section: Resultsmentioning
confidence: 99%
“…The only practical suggestion in this area has been allocating counseling sessions and support programs for students who need counseling [ 58 , 77 , 78 ].…”
Section: Opportunities Solutions and Knowledge In Dental Education After Facing Covid-19 Challengesmentioning
confidence: 99%
“…Supporting patients allow physicians, students (medical and dental), and nurses who are already stressed by the emergency load to serve humanity by treating the ailing community, 19 but it can also be emotionally draining. During the current pandemic, doctors are also cared for at home, mainly by their close family and relatives.…”
Section: Discussionmentioning
confidence: 99%